PEMERIKSAAN SKRINING KESEHATAN TENTANG PENYAKIT DEGENERATIF, PENYULUHAN TENTANG ETIKA BATUK DAN BERSIN SERTA PANDUAN CUCI TANGAN YANG BENAR, PEMBUATAN JUS BAWANG PUTIH DALAM PENYULUHAN KEFARMASIAN DI DESA BANJARSARI, CIAWI-BOGOR (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Public health is a major factor in improving quality of life. Disease prevention efforts, such as education on clean and healthy living behavior (PHBS), are important, especially in areas with limited access to information. The Community Service Program (KKN) in Banjarsari Village, Ciawi District, Bogor Regency, aims to increase public awareness through health education. This activity includes education on proper coughing and sneezing etiquette, hand washing practices according to WHO standards, and screening for degenerative diseases such as hypertension and diabetes. In addition, garlic juice was introduced as an herbal alternative for health. The results of the activity showed a positive response, especially from PAUD children, as well as increased public understanding of disease prevention. This program has a significant impact on increasing health literacy while enriching the experience of KKN participants in applying pharmaceutical science in the community.